Long-term objective assessments of skin rejuvenation using solar protection and solar repair shown through digital facial surface analysis and three-dimensional volumetric assessment - Tanaka Y (Dove Medical Press, 2019)
Yohei TanakaClinica Tanaka Plastic, Reconstructive Surgery and Anti-aging Center, Matsumoto, Nagano, JapanBackground: Despite the knowledge that the vast majority of skin aging is caused by the sun, and the widespread prevalence of sunscreen usage, solar skin damage continues to occur due to the combined biological impact of ultraviolet, visible light and near-infrared radiation. Sunscreens have only proven effective at filtering ultraviolet light. They do not attenuate visible light or near-infrared.Objective: To evaluate the effectiveness of a novel, solar-specific skincare approach embracing both comprehensive daily solar protection from ultraviolet through to near-infrared radiation and nightly solar repair.Participants: Eighteen Japanese patients were enrolled in this study. Topical skincare products (The Essential Six, RATIONALE, Victoria, Australia), comprising solar protection preparations to be used in the morning and topical solar repair at night, were applied to the patients’ skin for 12 months. Patients refrained from using any other skincare formulations and did not undergo any form of medical esthetic treatment during the study.Measurements: Digital facial skin and three-dimensional volumetric assessment were performed pre- and post-treatment, and patient assessments were recorded after 6 and 12 months post-treatment.Results: Improvements in skin texture and luminosity as recorded via digital photography, significant amelioration of skin redness and pigmentation in facial surface analysis, and volumetric reduction in three-dimensional volumetric assessment were observed compared to the pre-treatment for all patients. Eighty-nine percent, and 94% of patients self-reported their approval of treatment outcomes after 6 and 12 months post-treatment, respectively. Minor complications, characterized by slight pain and itching were observed in 3 patients. These minor complications resolved spontaneously.Conclusion: The results of this study indicate that the solar-specific skincare formulations focused on the daily comprehensive prevention of negative solar effects and nightly repair of photodamage provide a safe and highly effective pathway to skin preservation and rejuvenation.Keywords: long-term objective assessment, rejuvenation, solar protection, solar repair, sunscreen, volumetric measurement